FAMILY TAKAFUL (ISLAMIC LIFE INSURANCE) IN BANGLADESH: OPERATIONAL DILEMMAS AND REMEDIAL APPROACHES - DR. ISSA KHAN; MD. MAHFUJUR RAHMAN; DR. AZIAN BIN MADUN (Hamdard Islamicus, 2025)
Takaful industry in Bangladesh has been facing numerous problems. The study explores the operational dilemmas of family Takaful (Islamic life insurance) in Bangladesh and recommends approaches to meet the challenges. A qualitative method is used in this study, using data from thirty-two respondents, along with officers and SharÊ‘ah board members of Takaful companies, as well as Takaful participants. The findings revealed a lack of legislation, regulations, and policies for the development family Takaful in Bangladesh. Furthermore, mismanagement and profit-driven activities have adversely affected the family Takaful industry in Bangladesh. The ignorance of participants about the family Takaful is another setback in establishing a sustainable Takaful industry in Bangladesh. The study proposed strategies to overcome the challenges such as the family Takaful industry in Bangladesh may use commercial contracts that give SharÊ‘ah-specific funding and adopt different models of Takaful in accordance with the legislation of Malaysia. The findings of the research will be immensely useful in overcoming the constraints that the family Takaful in Bangladesh is now confronting.